Lack of Tularemia Among Health Care Providers With Close Contact With Infected Patients—A Case Series. (19th November 2019) - Nelson, Christina A; Brown, Jennifer; Riley, Linda; Dennis, Anne; Oyer, Ryan; Brown, Catherine
Abstract: Francisella tularensis has a low infectious dose and can infect laboratory staff handling clinical specimens. The risk to health care providers exposed during patient care is poorly defined. We describe 9 examples of health care providers who did not develop tularemia after significant exposures to infected patients.